2022
DOI: 10.3389/fonc.2022.898605
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-Based Nanoplatforms: The Emerging Tools for Breast Cancer Therapy

Abstract: Breast cancer (BC) remains the leading malignant tumor type among females worldwide. The patients with BC are still faced with undesirable metastasis, relapse rate, and drug resistance. Exosomes are defined as naturally occurring extracellular vesicles (EVs) with typical biomarkers that reflect the characteristics of the parent cells. Exosomes are crucial mediators involved in intercellular communication. By transferring multiple cargoes, represented by proteins, nucleic acids, lipids, metabolites, exosomes co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…Therefore, identification of specific markers associated with different exosome populations is of key importance. Application of exosome-based nanoplatforms have been suggested in breast cancer therapy as well [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, identification of specific markers associated with different exosome populations is of key importance. Application of exosome-based nanoplatforms have been suggested in breast cancer therapy as well [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Depending on existing disease states, exosomes can carry disorder-specific biomarkers that can allow them to be used as early-stage prognosis platforms (Hossain et al, 2022;Hsu et al, 2022;Hu et al, 2022;Yi et al, 2022). However, diseaseassociated biomarkers and proteins carried by exosomes can also partially impair normal physiological signaling pathways and speed up metastasis and tumor angiogenesis by taking part in intercellular crosstalk between tumor cells and nearby stromal cells (Wu et al, 2019a;Wu et al, 2019b;Liu et al, 2022). Accordingly, growth factor-containing exosomes derived from tumor cells are capable of enhancing cancer cell proliferation and differentiation by transferring their parent cells' information (such as inflammatory markers, growth factors, and miRNAs) to distant malignant cells and hence contribute to the progression of cancer (Maia et al, 2018;Eble and Niland, 2019;Liu et al, 2021).…”
Section: Exosomes' Immunomodulation Properties and Immunotherapeutic ...mentioning
confidence: 99%
“…For instance, exosome engineering, loading with specific biomolecules, and exosome-based drug delivery systems serve as potential immunotherapeutic platforms that are capable of manipulating immune responses in favor of disease treatment (Wang et al, 2015). Owing to their low immunogenicity, nanoscale dimensions, and carrier characteristics, exosomes are now increasingly employed in the development of cancer immunotherapeutics, cancer vaccines, and drug delivery (Yuan et al, 2019;Li et al, 2020b;Lindenbergh et al, 2020;Li et al, 2021;Liang et al, 2021;Liu et al, 2022). Seo Et al., indicated that the administration of exosomes originating from CD8 + T cells has significantly reduced metastasis and fibroblastic stroma-mediated tumor invasion in melanoma mouse models (Seo et al, 2018).…”
Section: Exosomes' Immunomodulation Properties and Immunotherapeutic ...mentioning
confidence: 99%
“…The application of exosome-enveloped AAV could prevent AAV capsid recognition by CD8 + cells and Toll-like receptors and neutralization by antibodies resulting in higher transduction efficiency [ 139 ]. Exosomes are very promising tools for the delivery of RNAi, mRNA or DNA for cancer therapy [ 140 , 141 ].…”
Section: Bringing Intrabodies Into Cancer Patients: Delivery Of Intra...mentioning
confidence: 99%